Adaptive immune cells and kidney function in older adults: sex-specific associations in the health and retirement study (HRS) - Shannon M. Sullivan; Bibin Joseph; Shweta Sharma; Weihua Guan; Amy B. Karger; Jessica Faul; Bharat Thyagarajan (Frontiers in Aging, 2026)
Background Chronic kidney disease (CKD) is characterized by chronic inflammation and immune dysregulation. Aging of the adaptive immune system, marked by a shift from naïve to memory T-cell phenotypes, is associated with systemic “inflammaging”, but sex-specific associations between these immunophenotypes and kidney function in older adults remain poorly understood. Methods We analyzed cross-sectional data from 8,970 participants (aged ≥56 years) in the 2016 Health and Retirement Study (HRS) Venous Blood Study. Seventeen adaptive immune cell subsets were quantified using multiparameter flow cytometry. Kidney function was assessed using estimated glomerular filtration rate (eGFR, mL/min/1.73 m 2 ) calculated from the 2021 race-free CKD-EPI creatinine-cystatin C equation. Survey-weighted linear regression models were adjusted for age, race/ethnicity, education, body-mass index (BMI), clinical comorbidities (diabetes, elevated blood pressure/hypertension), alcohol use, smoking status, and cytomegalovirus (CMV) serostatus. Sex-stratified analyses were conducted a priori , and sex interaction terms were evaluated to assess effect modification. Results Females were older and more likely to be never smokers, CMV seropositive, and have lower eGFR, whereas males were more likely to use alcohol, smoke, have diabetes, elevated blood pressure/hypertension and higher educational attainment. In sex-stratified models, higher CD4 + T cells (β = 0.96, P FDR = 0.010), CD8 + naïve T cells (β = 0.87, P FDR = 0.026), Ratio of CD4 + to CD8 + T cells (β = 0.73, P FDR = 0.036), and lymphocytes (β = 2.42, P FDR <0.001) were associated with higher eGFR (higher kidney function) in females, while higher CD4 + effector memory T cells (Tem; β = −1.58, P FDR = 0.010), CD8 + effector T cells (Teff; β = −1.00, P FDR = 0.004), and CD8 + Tem (β = −1.40, P FDR = 0.002) were associated with lower eGFR (lower kidney function). In males, higher IgD + memory B cells (β = 1.01, P FDR = 0.005), IgD− memory B cells (β = 1.04, P FDR = 0.011), and lymphocytes (β = 2.08, P FDR <0.001) were associated with higher eGFR. Significant sex interaction was observed for CD8 + Tem (P FDR = 0.015), with a nominal interaction for CD8 + Teff (P FDR = 0.060). Associations were similar in sensitivity analyses and were not modified by CMV serostatus. Conclusion Findings suggest that CD8 + Tem and Teff T cells may serve as sex-specific biomarkers of renal vulnerability in postmenopausal females and underscore the need for longitudinal and mechanistic studies to clarify underlying pathways.